Factors Associated to Pap Smear Cervical Screening Behavior among Midwives in Yogyakarta, Indonesia - Niken Meilani; Nanik Setiyawati (JURNAL KEBIDANAN, 2022)
Cervical cancer was the fourth most frequent cancer and approximately 90% of death occurred in low- and middle-income countries. Indonesia was the second country which has the most cervical cancer cases in the world. One recommended method of cervical cancer screening was pap smear test. This study aims to determine the factors that associated in midwive’s pap smear behavior. This study used a quantitative cross-sectional design. Subjects were 65 midwives in primary health care in Yogyakarta City.  Combination Theory used Precede and Procede and Health Belief Model. This research analysis  used univariate, bivariate and multivariate analysis. The results showed that there were 61.5% of midwives have did implementation of pap smear. There was a relationship between age (p=0.002), attitude (p=0.028), cost (p=0.208) and vulnerability (p=0.001) with pap smear behavior. There was no correlation between value  (p=0.724), benefit (p=0.403) and severity (p=0.813) with pap smear behavior. Multivariate analysis showed that age was the most dominant factors affecting pap smear behavior (p-value 0.009; PR 26.903; CI 95% 2.251-321.490). Need to improved promotive efforts about pap smear among midwives and also women in general.